Patterns and processes of variation of a rocky bottom cryptobethic fish assemblage - Beldade, Manuel Ricardo do Ó de Oliveira (2005)
The population dynamics of criptobentic fishes in the Arrábida Marine Park was investigated. The fluctuations in composition and abundance, the duration of the pelagic phase and the choice of settlement habitats were assessed. A new non-destructive technique to count cryptobenthic fishes was tested. To study the larval phase we sampled the shallow rocky subtidal where we found mostly cryptobenthic species. Some of these species remain close to shore throughout the entire pelagic phase, e.g. Pomatoschistus pictus. The duration of the period spent in the plankton is variable within the cryptobenthic fishes but there are some, such as the Gobiesocidae, that spend very short periods as larvae. Lepadogaster lepadogaster settlers occur in higher abundances in high complexity habitats. An interference visual technique was described, tested and used to describe the composition of the cryptobenthic assemblage and assess its spatio-temporal variation. Several species use a restricted number of habitats (e.g. Gobius xanthocephalus and Tripterygion delaisi), whereas only one used all habitats available, Parablennius pilicornis. Moreover, the habitat utilization changed seasonally. Diversity and abundance of the cryptobenthic assemblage remained stable during two years and a consistent seasonal trend was observed. The peek in abundance coincided with the arrival of recruits, in the autumn, but there was a clear decrease in abundance in the subsequent seasons. The population dynamics of cryptobenthic fishes seems to be structured by post-settlement processes and can be understood by the particular ecological features displayed throughout their life-cycle.